2013
DOI: 10.1073/pnas.1214786110
|View full text |Cite
|
Sign up to set email alerts
|

Governance regime and location influence avoided deforestation success of protected areas in the Brazilian Amazon

Abstract: Protected areas in tropical countries are managed under different governance regimes, the relative effectiveness of which in avoiding deforestation has been the subject of recent debates. Participants in these debates answer appeals for more strict protection with the argument that sustainable use areas and indigenous lands can balance deforestation pressures by leveraging local support to create and enforce protective regulations. Which protection strategy is more effective can also depend on (i) the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
300
2
21

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(349 citation statements)
references
References 39 publications
26
300
2
21
Order By: Relevance
“…Second, our interdisciplinary team had the requisite data to credibly estimate the effects of protected areas on carbon in all four countries, and to contrast those effects with the effects on poverty in neighboring communities in three of the four countries. All four countries have been the subjects of previous studies on the impact of protected areas on deforestation and regrowth (23,25,29,32). Two of them have been the subjects of published studies on the impact of protected areas on poverty in neighboring communities (31,32), and on the moderators of the forest and poverty impacts (26,37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our interdisciplinary team had the requisite data to credibly estimate the effects of protected areas on carbon in all four countries, and to contrast those effects with the effects on poverty in neighboring communities in three of the four countries. All four countries have been the subjects of previous studies on the impact of protected areas on deforestation and regrowth (23,25,29,32). Two of them have been the subjects of published studies on the impact of protected areas on poverty in neighboring communities (31,32), and on the moderators of the forest and poverty impacts (26,37).…”
Section: Methodsmentioning
confidence: 99%
“…Protected areas are also integral parts of strategies to reduce carbon emissions from deforestation and degradation, such as the REDD+* program (21,22). Recent studies have estimated the effects of terrestrial protected area networks on deforestation (23)(24)(25)(26)(27), fire (28), regrowth (29), and poverty (30-32), but not their effects on ecosystem services. Explicitly estimating effects on ecosystem services is important, because there is no reason to assume that the spatial variability of effects on ecosystem services matches the spatial variability of effects on human behaviors; for example, the spatial variability of carbon is highly heterogeneous (18,33), and the locations where carbon density is highest might not be the same locations where protected areas have the greatest effects on land use.…”
Section: Significancementioning
confidence: 99%
“…The United Nations (UN) [1] recognizes that there are over 370 million Indigenous people in at least 90 countries, still undertaking unique practices distinct from those of surrounding dominant societies. Emerging research shows the fundamental role of Indigenous land-use practices for controlling deforestation and reducing CO 2 emissions-analysis of satellite imagery suggests that Indigenous lands have reduced rates of deforestation and habitat conversion, and lower greenhouse gas (GHG) emissions, compared with surrounding areas [2][3][4][5]. Stevens et al [6], for example, found that in Bolivia, from 2000 to 2010, only 0.5% of the land area of Indigenous territories were deforested, compared with 3.2% overall in the Bolivian Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that ICCAs equal or exceed the number and extent of state protected areas and there is increasing evidence that under certain conditions (Ostrom, 1990(Ostrom, , 2000, areas and resources under the governance and/or management of Indigenous peoples and local communities can be, with certain scalespecific qualifications (Shahabuddin & Rao, 2010), as or more effective than strictly protected areas at preventing deforestation, maintaining forest health and ecosystem connectivity, and conserving biodiversity and natural resources (Kothari et al, 2000;Lovgren, 2003; Governance types White et al, 2004;Hayes & Ostrom, 2005;Nepstad et al, 2006;Nagendra, 2008;World Bank, 2008;Bray et al, 2008;Nelson & Chomitz, 2011;PorterBolland et al, 2011;Nolte et al, 2013;CIPTA & WCS, 2013;Stevens, 2014). In the context of the downward trends in global biodiversity Ceballos et al, 2017), therefore, appropriately recognising and supporting ICCAs becomes ever more important.…”
Section: Icca Require Greater Recognition and Supportmentioning
confidence: 99%
“…Exactly how this issue is resolved, and the way in which OECMs support the Pathway to Target 1's aims, will contribute to the discussion of a range of the issues raised in this paper. One potential challenge is that governance authorities of potential OECMs will be called upon to demonstrate, among other things: the identification of the full range of key biodiversity attributes for which the site qualifies; effective and enduring in-situ conservation of biodiversity (Stolton & Dudley, 2006;Nolte et al, 2013;Carranza et al, 2014;; a direct causal link between the area's longterm management and the conservation outcomes; and effective means of control over activities that could impact biodiversity. These requirements raise conceptual and practical questions.…”
Section: Example 2 Biodiversity Target 1 Canadamentioning
confidence: 99%